Organizational climate and work engagement in secondary level teachers in the Junín region - Espejo-Eslava, Deyanira M. (2022)
Objective. To establish the relationship between organizational climate and work engagement in secondary school teachers in the Junín region (Peru). Methods. The study had a quantitative approach, basic type for its purpose, correlational level and cross-sectional and correlational design. Two instruments were used: the organizational climate questionnaire which consisted of 23 items and whose dimensions were leadership, communication and motivation; and the work engagement questionnaire which consisted of 16 items and 3 dimensions: vigor, dedication and absorption. The sampling technique was non-probabilistic by convenience, and the sample consisted of 126 secondary school teachers. Results. 84.1 % perceived that the organizational climate was good and 69 % considered that work engagement was high. The hypothesis test confirms the significant relationship between both variables, since the p-value found was 0.001 and the Kendall's tau-b correlation strength was 0.363, which indicates that there is a medium-low correlation. Conclusion. There is sufficient evidence to affirm that the organizational climate has a lower level of incidence on work engagement, which, however, could be greater if educational institutions do not consider preventive measures.